HUBUNGAN MOBILISASI DINI PADA IBU POSTPARTUM DENGAN SECTIO CAESAREA METODE ERACS TERHADAP PENURUNAN INTENSITAS NYERI LUKA OPERASI DI RS PKU MUHAMMADIYAH GAMPING - Subaika Fitriana Rahman ,; Fitnaningsih Endang Cahyawati ,; Sholaikhah Sulistyaningtyas , (Journal of Innovation Research and Knowledge, 2025)
According to the World Health Organization (WHO), stated that the Sectio Caesarea operation is around 5-15% per 1000 births, in 2023 it showed 32.4% and in America the highest contributor with a figure of 40.5%. In developing countries 46.1%, In Indonesia in the city 11% much higher than in the village which is 3.9%, DKI Jakarta 14.8%, Bali Province 9.59%, Riau Province 7.72% and the Special Region of Yogyakarta as much as 28.26%. Purpose: research to determine the Relationship of Early Mobilization in Postpartum Mothers with Sectio Caesarea ERACS Method to Reducing the Intensity of Surgical Wound Pain at PKU Hospital. Method: this research is a type of quantitative research, with a correlational research design with a Cross Sectional approach. The sampling technique uses total sampling. The respondents of this study were 25 Postpartum mothers with Sectio Caesarea ERACS Method. The tools used in early mobilization are questionnaires and pain intensity assessment sheets Numeric Rating Scale (NRS). Data analysis using the Spearman Rank statistical test. Results: This study shows early mobilization in postpartum mothers with Sectio Caesarea ERACS method from 25 respondents, 24 respondents were early mobilization with good (96%) and 1 respondent early mobilization with poor (4%). The intensity of surgical wound pain. 6 respondents had mild pain (24%), 18 respondents had moderate pain (72%) and 1 respondent had severe pain (4%). Conclusion: There is a relationship between early mobilization and decreased pain intensity of surgical wounds with a p-value of 0.03 <0.05